A novel electrospun biphasic scaffold provides optimal three-dimensional topography forin vitroco-culture of airway epithelial and fibroblast cells - Morris, G.E.; Bridge, J.C.; Brace, L.A.; Knox, A.J.; Aylott, Jonathan W.; Brightling, C.E.; Ghaemmaghami, Amir M.; Rose, Felicity R.A.J. (IOP Publishing, 2014)
Conventional airway in vitro models focus upon the function of individual structural cells cultured in a two-dimensional monolayer, with limited three-dimensional (3D) models of the bronchial mucosa. Electrospinning offers an attractive method to produce defined, porous 3D matrices for cell culture. To investigate the effects of fibre diameter on airway epithelial and fibroblast cell growth and functionality, we manipulated the concentration and deposition rate of the non-degradable polymer polyethylene terephthalate to create fibres with diameters ranging from nanometre to micrometre. The nanofibre scaffold closely resembles the basement membrane of the bronchiole mucosal layer, and epithelial cells cultured at the air–liquid interface on this scaffold showed polarized differentiation. The microfibre scaffold mimics the porous sub-mucosal layer of the airway into which lung fibroblast cells showed good penetration. Using these defined electrospinning parameters we created a biphasic scaffold with 3D topography tailored for optimal growth of both cell types. Epithelial and fibroblast cells were co-cultured onto the apical nanofibre phase and the basal microfibre phase respectively, with enhanced epithelial barrier formation observed upon co-culture. This biphasic scaffold provides a novel 3D in vitro platform optimized to mimic the different microenvironments the cells encounter in vivo on which to investigate key airway structural cell interactions in airway diseases such as asthma.